Prevalence of obesity and diabetes among health care physicians in Pondicherry, India - Shankar, Sethu Prabhu; Uma Sudhan, E.; Reddy, K. Harsha Vardhan; Singh, Rahul; Ramya, Neelakandan (International Journal of Advances in Medicine, 2019)
Background: Non communicable diseases like obesity and diabetes are increasing worldwide, healthcare physicians are also not immune to this morbidity. The objective of this study is to find the prevalence of obesity and diabetes among healthcare physicians. Methods: The study was done at a tertiary care hospital in Pondicherry. All adult health care physicians of both sexes working in the hospital and giving informed consent to participate in the study were included. Pregnant physicians and those who are not willing to give written consent for participation in the study were excluded from the study. The study was done as a cross sectional study using a pretested standardized questionnaire. Age, sex, demographic data, height, weight, diet habits, family history of diabetes, exercise, medication in all the health care physicians were recorded and studied. Results: Of the total one hundred health care physicians, there were 50 male and 50 female physicians. Among the female physicians, there were 17 of age 41 to 50 years. There were 27 male and 34 female physicians with body mass index of 25 to 29.9. Six males and four females had diabetes mellitus. Six physicians were doing regular exercise. Four physicians were taking both oral anti hyperglycemic drugs and insulin. Conclusions: Doctors are aware and educated part of the society but there is high prevalence of obesity and diabetes mellitus among healthcare physicians. Doctor have to be motivated to take care of their health and to prevent lifestyle disease complication. Further regular screening for diabetes and obesity has to be done for doctors.